A simulation-optimization model for liquefied natural gas transportation considering product variety. Issue 4 (2nd October 2021) - Shafipour-Omrani, Bahareh; Rashidi Komijan, Alireza; Ghasemi, Peiman; Ghasemzadeh, Ebrahim; Babaeinesami, Abdollah
ABSTRACT: In this paper, the ports of origin and destination and transportation of the LNG supply chain are focused, and a model is presented to minimize the cost of sending natural gas from the primary port to the destination port, taking into account product diversity. Therefore the main research questions are as follows: What is the allocation of a loading port to the group of unloading ports? What are the optimal transportation costs for liquefied natural gas ships? This research holds innovation in two aspects, one is considering the product variety and the way of presenting the constraint (which differs from other studies in the field of liquefied natural gas), and the other is applying the actual events in the simulation-optimization model. To solve the proposed model, the branch and bound method is used and then different scenarios are designed and implemented for it with the help of simulation. The results show that the proposed solutions are appropriate and reduce transportation costs by about 11%. To clarify the computational capability and operating conditions of the model, the gas platforms of Iran and London were studied. This study shows that if the ships capacity increases and the product variation decreases, the number of times the ship leaves port are 30, the transportation cost is reduced by $ 221, 661.50 at the same time, the power of responding to demands will increase.